Fin de siècle Beirut : the making of an Ottoman provincial capital - Hanssen, Jens (Oxford historical monographs., 2005)
Combining urban theory with postcolonial methodology, Jens Hanssen argues that modern Beirut is the outcome of persistent social and intellectual struggles over the production of space.